2022
DOI: 10.3390/cells11172655
|View full text |Cite
|
Sign up to set email alerts
|

Differential Epigenetic Status and Responses to Stressors between Retinal Cybrids Cells with African versus European Mitochondrial DNA: Insights into Disease Susceptibilities

Abstract: Mitochondrial (mt) DNA can be classified into haplogroups, which represent populations with different geographic origins. Individuals of maternal African backgrounds (L haplogroup) are more prone to develop specific diseases compared those with maternal European-H haplogroups. Using a cybrid model, effects of amyloid-β (Amyβ), sub-lethal ultraviolet (UV) radiation, and 5-Aza-2′-deoxycytidine (5-aza-dC), a methylation inhibitor, were investigated. Amyβ treatment decreased cell metabolism and increased levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 74 publications
(99 reference statements)
0
1
0
Order By: Relevance
“… 43 This same group followed-up this initial study and recently reported that cybrids with the African and European haplogroup have different responses, including inflammatory pathways, to the stressors, amyloid-β, and sublethal ultraviolet radiation doses. 68 These studies indicate that mtDNA haplogroups can modulate gene expression, which can potentially lead to different responses to stress and perhaps susceptibility to specific diseases.…”
Section: Discussionmentioning
confidence: 99%
“… 43 This same group followed-up this initial study and recently reported that cybrids with the African and European haplogroup have different responses, including inflammatory pathways, to the stressors, amyloid-β, and sublethal ultraviolet radiation doses. 68 These studies indicate that mtDNA haplogroups can modulate gene expression, which can potentially lead to different responses to stress and perhaps susceptibility to specific diseases.…”
Section: Discussionmentioning
confidence: 99%